ISLAMIC EDUCATIONAL PHILOSOPHY “The Role of Philosophy in PAI Curriculum Development” - Ajat Saputra; Badru Sohim; Helmawati Helmawati; Iyad Suryadi (International Journal of Teaching and Learning, 2025)
Islamic Religious Education (PAI) has a strategic role in shaping the character, morals, and spirituality of students. However, the implementation of PAI curriculum in the field still tends to emphasize cognitive aspects, thus neglecting affective and psychomotor dimensions. This article aims to examine the role of Islamic education philosophy in the development of PAI curriculum to be more holistic, contextual, and transformative. This research uses a library research method with a descriptive-analytical approach to the thoughts of the figures and relevant literature. The results show that the philosophical foundations-ontological, epistemological, and axiological-contribute greatly to formulating the direction, content, methods, and evaluation of PAI curriculum. The ontological foundation emphasizes the development of human potential as a whole; the epistemological demands integration between revelation, reason, and experience; while the axiological prioritizes Islamic moral and ethical values in education. Thus, the philosophy of Islamic education becomes an important foundation in building PAI curriculum that is not only instructional, but also loaded with transcendental and humanistic values.